New material modified sound-proof room acoustic board and preparation method thereof
By preparing flame-retardant modified cellulose aerogel, combining foaming technology and flame retardant elements, the sound absorption and flame retardant performance of the sound-absorbing plate of the sound-absorbing chamber are improved, and the problems of limited sound absorption performance and poor flame retardant performance of the sound-absorbing plate are solved, achieving safe application in complex environments.
Patent Information
- Application Number
- CN202510569700.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-05
- Publication Date
- 2025-07-18
AI Technical Summary
The existing sound insulation chamber sound absorption panels have limited sound absorption performance and poor flame retardant performance, which cannot meet the needs of complex acoustic environments, and there is a burning risk in the event of fire.
Flame-retardant modified cellulose aerogel is used as the main raw material to prepare amino phosphorus-containing intermediates through reactions of dimethyl phosphite and acrylamide, and then react with epoxychlorohydrin to form a phosphorus-nitrogen crosslinking agent, and foam it in combination with sodium dodecyl sulfate to form a fine connected bubble structure, and the synergistic action of phosphorus, nitrogen elements and magnesium hydroxide is used to improve flame retardant performance.
It realizes the efficient sound absorption effect and excellent flame retardant performance of the sound absorbing plate, reduces noise interference, and effectively prevents the spread of flame during fire and ensures safety.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the field of sound-absorbing materials, and particularly to a new material modified sound-absorbing panel for a sound-insulating chamber and a preparation method thereof. Background Art
[0002] The modern building environment is becoming increasingly complex, and the environmental protection requirements are constantly increasing. The design and application of sound-absorbing materials have become an important research direction in the construction field. In the field of acoustics, the performance of the sound-absorbing panel in a sound-insulating chamber is directly related to the comfort of the building space and the sense of security of users.
[0003] At present, although there are many types of sound-absorbing panels on the market, there are many defects. Some sound-absorbing panels have limited sound-absorbing performance, and it is difficult to achieve efficient sound absorption, which cannot meet the requirements of complex acoustic environments. Moreover, most traditional sound-absorbing panels have poor flame retardancy, and are prone to burning and releasing toxic and harmful gases in case of fire, posing a serious threat to the lives and property safety of people.
[0004] Therefore, the development of a new material modified sound-absorbing panel for a sound-insulating chamber and a preparation method thereof is of great significance for improving the sound-absorbing performance and flame retardancy of the sound-absorbing panel in the sound-insulating chamber. Summary of the Invention
[0005] In order to overcome the above technical problems, the purpose of the present invention is to provide a new material modified sound-absorbing panel for a sound-insulating chamber and a preparation method thereof, which solves the problems of limited sound-absorbing performance and poor flame retardancy of the existing sound-absorbing panel in the sound-insulating chamber.
[0006] The purpose of the present invention can be achieved by the following technical solutions: A new material modified sound-absorbing panel for a sound-insulating chamber, comprising the following components in parts by weight: 20-36 parts of flame-retardant modified cellulose aerogel, 1.3-2.9 parts of calcium stearate, 40-48 parts of deionized water, 21-27 parts of epoxy resin, 2.5-4.5 parts of curing agent, 1.1-1.5 parts of sodium dodecyl sulfate, 0.8-1.2 parts of gelatin, and 0.3-0.5 parts of antioxidant; Wherein, the flame-retardant modified cellulose aerogel is prepared by the following steps: Step a1: Dimethyl phosphite, dioxane, and acrylamide are added into a three-necked flask equipped with a stirrer, a thermometer, a gas pipe, and a constant-pressure dropping funnel. Nitrogen is introduced for protection. The mixture is stirred and reacted for 20 - 30 min under the conditions of a temperature of 25 - 30 °C and a stirring rate of 300 - 400 r / min. Then, while stirring, a sodium methoxide - methanol solution is added dropwise, controlling the dropping rate at 1 - 2 drops / s. After the addition is complete, the temperature is raised to 40 - 45 °C and stirring and reaction continue for 20 - 30 min. Then, the temperature is raised to 80 - 85 °C and stirring and reaction continue for 5 - 6 h. After the reaction ends, the reaction product is cooled to 0 - 5 °C, then vacuum filtered. The filter cake is washed with anhydrous tetrahydrofuran 2 - 3 times, and then placed in a vacuum drying oven and dried at a temperature of 60 - 65 °C for 3 - 4 h to obtain an amino phosphorus-containing intermediate; Step a2: The amino phosphorus-containing intermediate, benzyltriethylammonium chloride, and epichlorohydrin are added into a three-necked flask equipped with a stirrer, a thermometer, and a gas pipe. Nitrogen is introduced for protection. The mixture is stirred and reacted for 20 - 30 min under the conditions of a temperature of 25 - 30 °C and a stirring rate of 300 - 400 r / min. Then, the temperature is raised to 110 - 120 °C and stirring and reaction continue for 2 - 3 h. Then, the temperature is lowered to 50 - 55 °C, and a sodium hydroxide solution is added to adjust the pH to 9 - 10. Then, stirring and reaction continue for 5 - 6 h. After the reaction ends, the reaction product is cooled to room temperature, then extracted with toluene 3 - 5 times. The extraction liquids are combined and dried with anhydrous sodium sulfate, then vacuum filtered. The filtrate is rotary evaporated to remove the solvent to obtain a phosphorus-nitrogen crosslinking agent; Step a3: Sodium hydroxide, urea, and deionized water are added into a three-necked flask equipped with a stirrer and a thermometer. The mixture is stirred and reacted for 40 - 50 min under the conditions of a temperature of -5 - 0 °C and a stirring rate of 300 - 400 r / min. Then, cotton wool is added and stirring and reaction continue for 30 - 40 min. Then, the phosphorus-nitrogen crosslinking agent is added and the temperature is raised to 80 - 85 °C and stirring and reaction continue for 5 - 6 h. After the reaction ends, the reaction product is cooled to room temperature, then ultrasonically treated for 20 - 30 min under the condition of an ultrasonic power of 500 - 600 W, then poured into a mold, and then left to stand and solidify for 10 - 12 h to obtain a phosphorus-nitrogen modified cellulose hydrogel; Step a4: The phosphorus-nitrogen modified cellulose hydrogel is immersed in a magnesium chloride solution for 10 - 12 h, then taken out and immersed in a sodium hydroxide solution for 20 - 30 h, and then placed in a freeze dryer and freeze-dried at a temperature of -50 °C for 30 - 40 h to obtain a flame-retardant modified cellulose aerogel.
[0007] As a further solution of the present invention: the dosage ratio of dimethyl phosphite, dioxane, acrylamide and sodium methoxide - methanol solution in step a1 is 10 mmol: 30 - 35 mL: 10 mmol: 3 - 5 mL.
[0008] As a further solution of the present invention: the sodium methoxide - methanol solution in step a1 is a solution formed by dissolving sodium methoxide at 0.5 - 1 g: 10 mL in anhydrous methanol.
[0009] As a further solution of the present invention: the dosage ratio of the amino - phosphorus intermediate, benzyltriethylammonium chloride and epichlorohydrin in step a2 is 10 mmol: 0.05 - 0.15 g: 80 - 100 mmol.
[0010] As a further solution of the present invention: the mass fraction of the sodium hydroxide solution in step a2 is 30 - 40%.
[0011] As a further solution of the present invention: the dosage ratio of sodium hydroxide, urea, deionized water, cotton wool and the phosphorus - nitrogen cross - linker in step a3 is 3 - 4 g: 6 - 7 g: 40 - 45 mL: 5 g: 2.1 - 6.9 g.
[0012] As a further solution of the present invention: the dosage ratio of the phosphorus - nitrogen modified cellulose hydrogel, magnesium chloride solution and sodium hydroxide solution in step a4 is 5 g: 20 - 25 mL: 50 - 55 mL.
[0013] As a further solution of the present invention: the molar concentration of the magnesium chloride solution in step a4 is 0.5 - 1 mol / L; the mass fraction of the sodium hydroxide solution is 20 - 25%.
[0014] As a further solution of the present invention: a preparation method of a new material - modified sound - absorbing panel for a sound - insulating chamber, comprising the following steps: Step 1: Weigh 20 - 36 parts by weight of flame - retardant modified cellulose aerogel, 1.3 - 2.9 parts of calcium stearate, 40 - 48 parts of deionized water, 21 - 27 parts of epoxy resin, 2.5 - 4.5 parts of curing agent, 1.1 - 1.5 parts of sodium dodecyl sulfate, 0.8 - 1.2 parts of gelatin and 0.3 - 0.5 parts of antioxidant, and set aside; Step 2: Add the flame - retardant modified cellulose aerogel, calcium stearate and deionized water into a reaction kettle, stir and mix for 30 - 60 min under the condition that the stirring rate is 600 - 800 r / min, then add the epoxy resin, sodium dodecyl sulfate, gelatin and antioxidant and continue to stir and mix for 30 - 40 min to form a mixed slurry; Step 3: Add the curing agent into the mixed slurry and continue stirring for 10 - 15 min. Then pour it into a mold, place it in a vacuum drying oven, and dry it for 2 - 4 h at a temperature of 60 - 70 °C. After curing and forming, take it out and trim it to remove the excess scraps and burrs to obtain the new material modified sound absorption board for the sound insulation chamber.
[0015] As a further solution of the present invention: the epoxy resin is E - 44 epoxy resin; the curing agent is 593 curing agent; the antioxidant is antioxidant 1010.
[0016] The beneficial effects of the present invention: A new material modified sound absorption board for a sound insulation chamber and its preparation method of the present invention, by adding the flame - retardant modified cellulose aerogel, calcium stearate, and deionized water into a reaction kettle and stirring and mixing them, then adding the epoxy resin, sodium dodecyl sulfate, gelatin, and antioxidant and continuing to stir and mix to form a mixed slurry, adding the curing agent into the mixed slurry and continuing to stir and mix, then pouring it into a mold for drying, taking it out after curing and forming, and trimming it to obtain the new material modified sound absorption board for the sound insulation chamber; this sound absorption board uses the prepared new material, flame - retardant modified cellulose aerogel, as the main raw material, endows the sound absorption board with abundant pores, and uses sodium dodecyl sulfate as a surfactant - type foaming agent for foaming to further increase the number of internal micropores of the sound absorption board, forming a fine, uniform, and connected bubble structure inside the material, thereby providing a large number of reflection, scattering, and absorption interfaces for sound waves, effectively reducing noise interference, creating a good acoustic environment for the sound insulation chamber, and moreover, the flame - retardant modified cellulose aerogel has excellent flame - retardant properties, making the sound absorption board have good flame - retardant performance. In case of a fire, the sound absorption board can effectively prevent the spread of fire, reduce the fire risk, and ensure the safety of personnel and property. Moreover, the preparation process is simple, easy for large - scale production, and enables the sound absorption board for the sound insulation chamber to have excellent comprehensive performance and meet the application requirements under various complex environments.
[0017] In the process of preparing the sound-absorbing board of the new material modified soundproof room, a flame-retardant modified cellulose aerogel was first prepared. Dimethyl phosphite and acrylamide were used for reaction. The P-H on dimethyl phosphite underwent an addition reaction with the alkenyl group on acrylamide to obtain an amino phosphorus-containing intermediate. Then, the amino phosphorus-containing intermediate and epichlorohydrin were reacted. The amino group on the amino phosphorus-containing intermediate underwent a ring-opening and ring-closing reaction with epichlorohydrin, thereby introducing two epoxy groups to obtain a phosphorus-nitrogen cross-linking agent. Then, cotton wool was used as a raw material for extraction to obtain cellulose. Then, the cellulose was treated with the phosphorus-nitrogen cross-linking agent. The epoxy group on the phosphorus-nitrogen cross-linking agent reacted with the hydroxyl group on the cellulose, thereby fully cross-linking the cellulose to form a dense network structure, and at the same time introducing an organic phosphorus-nitrogen structure to obtain a phosphorus-nitrogen modified cellulose hydrogel. Then, the phosphorus-nitrogen modified cellulose hydrogel was immersed in a magnesium chloride solution to fully immerse magnesium ions. Then, magnesium hydroxide was formed under alkaline conditions, and the magnesium hydroxide was effectively loaded in the phosphorus-nitrogen modified cellulose hydrogel. Then, it was freeze-dried to form an aerogel, and a flame-retardant modified cellulose aerogel was obtained. The flame-retardant modified cellulose aerogel has a unique three-dimensional porous network structure. These pores are of different sizes and are interconnected. The sound waves entering the pores are continuously reflected and refracted inside the aerogel, and the energy of the sound waves will be continuously consumed, thereby achieving the sound-absorbing effect. Moreover, there are a large number of phosphorus and nitrogen elements in the flame-retardant modified cellulose aerogel. When the temperature rises, the phosphorus-containing compounds will decompose to form phosphoric acid, metaphosphoric acid, etc. These acids have strong dehydration properties and can dehydrate and carbonize the cellulose in the cellulose aerogel to form a dense carbon layer. The nitrogen-containing compounds will generate non-combustible gases such as nitrogen and ammonia when heated. These gases can dilute the oxygen concentration in the combustion area, reduce the concentration of combustible gases, and inhibit the progress of the combustion reaction. Moreover, a large amount of magnesium hydroxide is also loaded in the flame-retardant modified cellulose aerogel. Magnesium hydroxide will undergo a decomposition reaction when heated, absorb a large amount of heat, and will also decompose to generate a large amount of water vapor, which can dilute the oxygen and combustible gas concentrations in the combustion area. Therefore, under the synergistic action of phosphorus, nitrogen elements and magnesium hydroxide, it is given excellent flame-retardant properties. Detailed implementation mode
[0018] The following will combine the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative work belong to the scope of protection of the present invention.
[0019] Example 1: This example is a preparation method of a sound-absorbing board of a new material modified soundproof room, including the following steps: Step S1: Add 10 mmol of dimethyl phosphite, 30 mL of dioxane, and 10 mmol of acrylamide into a three-necked flask equipped with a stirrer, a thermometer, a gas pipe, and a constant-pressure dropping funnel. Introduce nitrogen for protection, and stir and react for 20 min at a temperature of 25 °C and a stirring rate of 300 r / min. Then, while stirring, gradually add dropwise 3 mL of a sodium methoxide-methanol solution formed by dissolving 0.5 g of sodium methoxide in 10 mL of anhydrous methanol, controlling the dropping rate at 1 drop / s. After the addition is complete, continue to stir and react at 40 °C for 20 min, and then continue to stir and react at 80 °C for 5 h. After the reaction is completed, cool the reaction product to 0 °C, then perform vacuum filtration. Wash the filter cake twice with anhydrous tetrahydrofuran, and then place it in a vacuum drying oven and dry at 60 °C for 3 h to obtain an amino phosphorus-containing intermediate; Step S2: Add 10 mmol of the amino phosphorus-containing intermediate, 0.05 g of benzyltriethylammonium chloride, and 80 mmol of epichlorohydrin into a three-necked flask equipped with a stirrer, a thermometer, and a gas pipe. Introduce nitrogen for protection, and stir and react for 20 min at a temperature of 25 °C and a stirring rate of 300 r / min. Then, continue to stir and react at 110 °C for 2 h, and then cool to 50 °C and add a 30% sodium hydroxide solution to adjust the pH to 9, and then continue to stir and react for 5 h. After the reaction is completed, cool the reaction product to room temperature, then extract it three times with toluene. Combine the extraction liquid and dry it with anhydrous sodium sulfate, then perform vacuum filtration, and rotary evaporate the filtrate to remove the solvent to obtain a phosphorus-nitrogen crosslinking agent; Step S3: Add 3 g of sodium hydroxide, 6 g of urea, and 40 mL of deionized water into a three-necked flask equipped with a stirrer and a thermometer. Stir and react for 40 min at a temperature of -5 °C and a stirring rate of 300 r / min. Then, add 5 g of cotton wool and continue to stir and react for 30 min. Then, add 2.1 g of the phosphorus-nitrogen crosslinking agent and continue to stir and react at 80 °C for 5 h. After the reaction is completed, cool the reaction product to room temperature, then perform ultrasonic treatment for 20 min under an ultrasonic power of 500 W, then pour it into a mold, and then let it stand and solidify for 10 h to obtain a phosphorus-nitrogen modified cellulose hydrogel; Step S4: Immerse 5 g of the phosphorus-nitrogen modified cellulose hydrogel in 20 mL of a magnesium chloride solution with a molar concentration of 0.5 mol / L for 10 h, then take it out and immerse it in 50 mL of a 20% sodium hydroxide solution for 20 h, and then place it in a freeze dryer and freeze-dry at -50 °C for 30 h to obtain a flame-retardant modified cellulose aerogel; Step S5: Weigh 20 parts of flame-retardant modified cellulose aerogel, 1.3 parts of calcium stearate, 40 parts of deionized water, 21 parts of epoxy resin, 2.5 parts of curing agent, 1.1 parts of sodium dodecyl sulfate, 0.8 part of gelatin, and 0.3 part of antioxidant, and set aside; the epoxy resin is E-44 epoxy resin; the curing agent is 593 curing agent; the antioxidant is antioxidant 1010; Step S6: Add the flame-retardant modified cellulose aerogel, calcium stearate, and deionized water to the reaction kettle, stir and mix for 30 min under the condition that the stirring rate is 600 r / min, and then add the epoxy resin, sodium dodecyl sulfate, gelatin, and antioxidant and continue to stir and mix for 30 min to form a mixed slurry; Step S7: Add the curing agent to the mixed slurry and continue to stir and mix for 10 min, then pour it into a mold, then place it in a vacuum drying oven, and then dry it at a temperature of 60 °C for 2 h. After curing and forming, take it out and trim it to remove excess scraps and burrs to obtain a new material modified sound insulation chamber sound absorption board.
[0020] Example 2: This example is a preparation method of a new material modified sound insulation chamber sound absorption board, including the following steps: Step S1: Add 10 mmol of dimethyl phosphite, 32 mL of dioxane, and 10 mmol of acrylamide to a three-necked flask equipped with a stirrer, thermometer, gas guide tube, and constant pressure dropping funnel, introduce nitrogen protection, and stir and react at a temperature of 28 °C and a stirring rate of 350 r / min for 25 min. Then, while stirring, gradually dropwise add 4 mL of a sodium methoxide-methanol solution formed by dissolving 0.8 g of sodium methoxide in 10 mL of anhydrous methanol, control the dropping rate at 1 drop / s, and after dropping, raise the temperature to 42 °C and continue to stir and react for 25 min. Then, raise the temperature to 82 °C and continue to stir and react for 5.5 h. After the reaction is completed, cool the reaction product to 3 °C, then carry out vacuum filtration, wash the filter cake with anhydrous tetrahydrofuran twice, and then place it in a vacuum drying oven and dry it at a temperature of 62 °C for 3.5 h to obtain an amino phosphorus-containing intermediate; Step S2: Add 10 mmol of amino phosphorus intermediate, 0.1 g of benzyltriethylammonium chloride, and 90 mmol of epichlorohydrin into a three-necked flask equipped with a stirrer, a thermometer, and a gas pipe. Introduce nitrogen for protection. Stir and react at a temperature of 28 °C and a stirring rate of 350 r / min for 25 min. Then, raise the temperature to 115 °C and continue to stir and react for 2.5 h. After that, lower the temperature to 52 °C and add a sodium hydroxide solution with a mass fraction of 35% to adjust the pH to 9.5. Then, continue to stir and react for 5.5 h. After the reaction is completed, cool the reaction product to room temperature. Then, extract it with toluene 4 times. Combine the extraction liquid and dry it with anhydrous sodium sulfate. Then, perform vacuum filtration. Rotate and evaporate the filtrate to remove the solvent to obtain a phosphorus-nitrogen crosslinking agent; Step S3: Add 3.5 g of sodium hydroxide, 6.5 g of urea, and 42 mL of deionized water into a three-necked flask equipped with a stirrer and a thermometer. Stir and react at a temperature of -3 °C and a stirring rate of 350 r / min for 45 min. Then, add 5 g of cotton wool and continue to stir and react for 35 min. Then, add 4.5 g of the phosphorus-nitrogen crosslinking agent and raise the temperature to 82 °C and continue to stir and react for 5.5 h. After the reaction is completed, cool the reaction product to room temperature. Then, perform ultrasonic treatment for 25 min under the condition of an ultrasonic power of 550 W. Then, pour it into a mold and let it stand and solidify for 11 h to obtain a phosphorus-nitrogen modified cellulose hydrogel; Step S4: Immerse 5 g of the phosphorus-nitrogen modified cellulose hydrogel in 22 mL of a magnesium chloride solution with a molar concentration of 0.8 mol / L for 11 h. Then, take it out and immerse it in 52 mL of a sodium hydroxide solution with a mass fraction of 22% for 25 h. Then, place it in a freeze dryer and freeze-dry it at a temperature of -50 °C for 35 h to obtain a flame-retardant modified cellulose aerogel; Step S5: Weigh 28 parts of the flame-retardant modified cellulose aerogel, 2.1 parts of calcium stearate, 44 parts of deionized water, 24 parts of epoxy resin, 3.5 parts of curing agent, 1.3 parts of sodium dodecyl sulfate, 1 part of gelatin, and 0.4 part of antioxidant, and set aside; the epoxy resin is E-44 epoxy resin; the curing agent is 593 curing agent; the antioxidant is antioxidant 1010; Step S6: Add the flame-retardant modified cellulose aerogel, calcium stearate, and deionized water into a reaction kettle. Stir and mix at a stirring rate of 700 r / min for 45 min. Then, add the epoxy resin, sodium dodecyl sulfate, gelatin, and antioxidant and continue to stir and mix for 35 min to form a mixed slurry; Step S7: Add a curing agent to the mixed slurry and continue stirring and mixing for 12 min. Then pour it into a mold, place it in a vacuum drying oven, and dry it at a temperature of 65 °C for 3 h. After curing and forming, take it out and trim it to remove excess scraps and burrs to obtain a new material modified sound insulation chamber sound absorption board.
[0021] Example 3: This example is a preparation method of a new material modified sound insulation chamber sound absorption board, including the following steps: Step S1: Add 10 mmol of dimethyl phosphite, 35 mL of dioxane, and 10 mmol of acrylamide into a three-necked flask equipped with a stirrer, a thermometer, a gas pipe, and a constant pressure dropping funnel. Pass in nitrogen for protection and stir and react at a temperature of 30 °C and a stirring rate of 400 r / min for 30 min. Then, while stirring, gradually dropwise add a sodium methoxide-methanol solution formed by dissolving 5 mL of sodium methoxide in 1 g:10 mL of anhydrous methanol, control the dropping rate at 2 drops / s. After dropping, raise the temperature to 45 °C and continue stirring and reacting for 30 min. Then raise the temperature to 85 °C and continue stirring and reacting for 6 h. After the reaction is completed, cool the reaction product to 5 °C, then perform vacuum filtration. Wash the filter cake with anhydrous tetrahydrofuran 3 times, and then place it in a vacuum drying oven and dry it at a temperature of 65 °C for 4 h to obtain an amino phosphorus-containing intermediate; Step S2: Add 10 mmol of the amino phosphorus-containing intermediate, 0.15 g of benzyltriethylammonium chloride, and 100 mmol of epichlorohydrin into a three-necked flask equipped with a stirrer, a thermometer, and a gas pipe. Pass in nitrogen for protection and stir and react at a temperature of 30 °C and a stirring rate of 400 r / min for 30 min. Then raise the temperature to 120 °C and continue stirring and reacting for 3 h. Then lower the temperature to 55 °C and add a sodium hydroxide solution with a mass fraction of 40% to adjust the pH to 10. Then continue stirring and reacting for 6 h. After the reaction is completed, cool the reaction product to room temperature, then extract it with toluene 5 times. Combine the extraction liquid and dry it with anhydrous sodium sulfate, then perform vacuum filtration. Rotate and evaporate the filtrate to remove the solvent to obtain a phosphorus-nitrogen crosslinking agent; Step S3: Add 4 g of sodium hydroxide, 7 g of urea, and 45 mL of deionized water into a three-necked flask equipped with a stirrer and a thermometer. Stir and react at a temperature of 0 °C and a stirring rate of 400 r / min for 50 min. Then add 5 g of cotton wool and continue stirring and reacting for 40 min. Then add 6.9 g of the phosphorus-nitrogen crosslinking agent and raise the temperature to 85 °C and continue stirring and reacting for 6 h. After the reaction is completed, cool the reaction product to room temperature, then perform ultrasonic treatment at an ultrasonic power of 600 W for 30 min. Then pour it into a mold and let it stand and solidify for 12 h to obtain a phosphorus-nitrogen modified cellulose hydrogel; Step S4: Immerse the 5g of phosphorus and nitrogen modified cellulose hydrogel in 25 mL of magnesium chloride solution with a molar concentration of 1 mol / L for 12 h, then take it out and immerse it in 55 mL of sodium hydroxide solution with a mass fraction of 25% for 30 h. Then place it in a freeze dryer and freeze-dry it at a temperature of -50 °C for 40 h to obtain a flame-retardant modified cellulose aerogel; Step S5: Weigh 36 parts of the flame-retardant modified cellulose aerogel, 2.9 parts of calcium stearate, 48 parts of deionized water, 27 parts of epoxy resin, 4.5 parts of curing agent, 1.5 parts of sodium dodecyl sulfate, 1.2 parts of gelatin, and 0.5 part of antioxidant according to weight, and set aside; the epoxy resin is E-44 epoxy resin; the curing agent is 593 curing agent; the antioxidant is antioxidant 1010; Step S6: Add the flame-retardant modified cellulose aerogel, calcium stearate, and deionized water to the reaction kettle, stir and mix at a stirring rate of 800 r / min for 60 min, then add epoxy resin, sodium dodecyl sulfate, gelatin, and antioxidant and continue to stir and mix for 40 min to form a mixed slurry; Step S7: Add the curing agent to the mixed slurry and continue to stir and mix for 15 min, then pour it into a mold, then place it in a vacuum drying oven, and then dry it at a temperature of 70 °C for 4 h. After curing and molding, take it out and trim it to remove excess scraps and burrs to obtain a new material modified sound-absorbing panel for a sound-insulated room.
[0022] Comparative Example 1: This comparative example is a preparation method of a new material modified sound-absorbing panel for a sound-insulated room, including the following steps: Step S1: Weigh 2.9 parts of calcium stearate, 48 parts of deionized water, 27 parts of epoxy resin, 4.5 parts of curing agent, 1.5 parts of sodium dodecyl sulfate, 1.2 parts of gelatin, and 0.5 part of antioxidant according to weight, and set aside; the epoxy resin is E-44 epoxy resin; the curing agent is 593 curing agent; the antioxidant is antioxidant 1010; Step S2: Add calcium stearate and deionized water to the reaction kettle, stir and mix at a stirring rate of 800 r / min for 60 min, then add epoxy resin, sodium dodecyl sulfate, gelatin, and antioxidant and continue to stir and mix for 40 min to form a mixed slurry; Step S3: Add the curing agent to the mixed slurry and continue to stir and mix for 15 min, then pour it into a mold, then place it in a vacuum drying oven, and then dry it at a temperature of 70 °C for 4 h. After curing and molding, take it out and trim it to remove excess scraps and burrs to obtain a new material modified sound-absorbing panel for a sound-insulated room.
[0023] Comparative Example 2: This comparative example is a preparation method of a sound-absorbing panel for a new material-modified sound-insulating chamber, including the following steps: Step S1: Add 4 g of sodium hydroxide, 7 g of urea, and 45 mL of deionized water into a three-necked flask equipped with a stirrer and a thermometer. Stir and react for 50 min under the conditions of a temperature of 0 °C and a stirring rate of 400 r / min. Then add 5 g of cotton wool and continue to stir and react for 40 min. Then raise the temperature to 85 °C and continue to stir and react for 6 h. After the reaction is completed, cool the reaction product to room temperature. Then, under the condition of an ultrasonic power of 600 W, perform ultrasonic treatment for 30 min. Then pour it into a mold and let it stand and solidify for 12 h to obtain a cellulose hydrogel; Step S2: Place 5 g of the cellulose hydrogel in a freeze dryer and freeze-dry it for 40 h under the condition of a temperature of -50 °C to obtain a cellulose aerogel; Step S3: Weigh 36 parts of cellulose aerogel, 2.9 parts of calcium stearate, 48 parts of deionized water, 27 parts of epoxy resin, 4.5 parts of curing agent, 1.5 parts of sodium dodecyl sulfate, 1.2 parts of gelatin, and 0.5 part of antioxidant for standby; the epoxy resin is E-44 epoxy resin; the curing agent is 593 curing agent; the antioxidant is antioxidant 1010; Step S4: Add the cellulose aerogel, calcium stearate, and deionized water into a reaction kettle and stir and mix for 60 min under the condition of a stirring rate of 800 r / min. Then add the epoxy resin, sodium dodecyl sulfate, gelatin, and antioxidant and continue to stir and mix for 40 min to form a mixed slurry; Step S5: Add the curing agent into the mixed slurry and continue to stir and mix for 15 min. Then pour it into a mold and place it in a vacuum drying oven. Then dry it at a temperature of 70 °C for 4 h. After curing and forming, take it out and trim it to remove excess scraps and burrs to obtain a sound-absorbing panel for a new material-modified sound-insulating chamber.
[0024] Comparative Example 3: This comparative example is a preparation method of a sound-absorbing panel for a new material-modified sound-insulating chamber, including the following steps: Step S1: Add 10 mmol of dimethyl phosphite, 35 mL of dioxane, and 10 mmol of acrylamide into a three-necked flask equipped with a stirrer, a thermometer, a gas pipe, and a constant-pressure dropping funnel. Introduce nitrogen for protection. Stir and react for 30 min under the conditions of a temperature of 30 °C and a stirring rate of 400 r / min. Then, while stirring, gradually add dropwise a sodium methoxide-methanol solution formed by dissolving 5 mL of sodium methoxide in 50 mL of anhydrous methanol (1 g:10 mL), control the dropping rate at 2 drops / s. After the addition is complete, continue to stir and react for 30 min under the condition of heating to 45 °C, and then continue to stir and react for 6 h under the condition of heating to 85 °C. After the reaction is completed, cool the reaction product to 5 °C, then perform vacuum filtration. Wash the filter cake 3 times with anhydrous tetrahydrofuran, and then place it in a vacuum drying oven and dry it for 4 h under the condition of a temperature of 65 °C to obtain an amino phosphorus-containing intermediate; Step S2: Add 10 mmol of the amino phosphorus-containing intermediate, 0.15 g of benzyltriethylammonium chloride, and 100 mmol of epichlorohydrin into a three-necked flask equipped with a stirrer, a thermometer, and a gas pipe. Introduce nitrogen for protection. Stir and react for 30 min under the conditions of a temperature of 30 °C and a stirring rate of 400 r / min. Then, continue to stir and react for 3 h under the condition of heating to 120 °C. Then, cool to 55 °C and add a 40% sodium hydroxide solution to adjust the pH to 10, and then continue to stir and react for 6 h. After the reaction is completed, cool the reaction product to room temperature, then extract it 5 times with toluene. Combine the extraction liquid and dry it with anhydrous sodium sulfate, then perform vacuum filtration. Rotate and evaporate the filtrate to remove the solvent to obtain a phosphorus-nitrogen crosslinking agent; Step S3: Add 4 g of sodium hydroxide, 7 g of urea, and 45 mL of deionized water into a three-necked flask equipped with a stirrer and a thermometer. Stir and react for 50 min under the conditions of a temperature of 0 °C and a stirring rate of 400 r / min. Then, add 5 g of cotton wool and continue to stir and react for 40 min. Then, add 6.9 g of the phosphorus-nitrogen crosslinking agent and continue to stir and react for 6 h under the condition of heating to 85 °C. After the reaction is completed, cool the reaction product to room temperature, then perform ultrasonic treatment for 30 min under the condition of an ultrasonic power of 600 W, then pour it into a mold, and then let it stand and solidify for 12 h to obtain a phosphorus-nitrogen modified cellulose hydrogel; Step S4: Place 5 g of the phosphorus-nitrogen modified cellulose hydrogel in a freeze dryer and freeze-dry it for 40 h under the condition of a temperature of -50 °C to obtain a flame-retardant modified cellulose aerogel; Step S5: Weigh 36 parts by weight of flame-retardant modified cellulose aerogel, 2.9 parts of calcium stearate, 48 parts of deionized water, 27 parts of epoxy resin, 4.5 parts of curing agent, 1.5 parts of sodium dodecyl sulfate, 1.2 parts of gelatin, and 0.5 part of antioxidant for standby; the epoxy resin is E-44 epoxy resin; the curing agent is 593 curing agent; the antioxidant is antioxidant 1010; Step S6: Add the flame-retardant modified cellulose aerogel, calcium stearate, and deionized water into a reaction kettle, stir and mix for 60 min under the condition of a stirring rate of 800 r / min, then add the epoxy resin, sodium dodecyl sulfate, gelatin, and antioxidant and continue to stir and mix for 40 min to form a mixed slurry; Step S7: Add the curing agent into the mixed slurry and continue to stir and mix for 15 min, then pour it into a mold, then place it in a vacuum drying oven, and then dry it for 4 h under the condition of a temperature of 70 °C. After curing and forming, take it out and trim it to remove excess scraps and burrs to obtain a new material modified sound insulation chamber sound absorption board.
[0025] Comparative Example 4: This comparative example is a preparation method of a new material modified sound insulation chamber sound absorption board, including the following steps: Step S1: Add 4 g of sodium hydroxide, 7 g of urea, and 45 mL of deionized water into a three-necked flask equipped with a stirrer and a thermometer, stir and react for 50 min under the conditions of a temperature of 0 °C and a stirring rate of 400 r / min, then add 5 g of cotton wool and continue to stir and react for 40 min, then raise the temperature to 85 °C and continue to stir and react for 6 h. After the reaction is completed, cool the reaction product to room temperature, then perform ultrasonic treatment for 30 min under the condition of an ultrasonic power of 600 W, then pour it into a mold, and then let it stand and solidify for 12 h to obtain cellulose hydrogel; Step S2: Immerse 5 g of cellulose hydrogel in 25 mL of magnesium chloride solution with a molar concentration of 1 mol / L for 12 h, then take it out and immerse it in 55 mL of sodium hydroxide solution with a mass fraction of 25% for 30 h, then place it in a freeze dryer and freeze-dry it for 40 h under the condition of a temperature of -50 °C to obtain flame-retardant modified cellulose aerogel; Step S3: Weigh 36 parts by weight of flame-retardant modified cellulose aerogel, 2.9 parts of calcium stearate, 48 parts of deionized water, 27 parts of epoxy resin, 4.5 parts of curing agent, 1.5 parts of sodium dodecyl sulfate, 1.2 parts of gelatin, and 0.5 part of antioxidant for standby; the epoxy resin is E-44 epoxy resin; the curing agent is 593 curing agent; the antioxidant is antioxidant 1010; Step S4: Add the flame-retardant modified cellulose aerogel, calcium stearate, and deionized water into a reaction kettle, stir and mix them for 60 min under the condition that the stirring rate is 800 r / min, and then add epoxy resin, sodium dodecyl sulfate, gelatin, and antioxidant and continue to stir and mix for 40 min to form a mixed slurry; Step S5: Add a curing agent into the mixed slurry and continue to stir and mix for 15 min, then pour it into a mold, then place it in a vacuum drying oven, and then dry it for 4 h under the condition that the temperature is 70 °C. After curing and molding, take it out and trim it to remove excess edge materials and burrs to obtain a new material modified sound-absorbing panel for a soundproof chamber.
[0026] Perform performance tests on the new material modified sound-absorbing panels of Examples 1-3 and Comparative Examples 1-4. Use the standing wave tube method and a SWTM01-X sound absorption coefficient tester to measure the sound absorption coefficients at frequencies of 2000 Hz and 4000 Hz; use a J-3 type limiting oxygen index instrument to measure the limiting oxygen index. The test results are shown in the following table:
[0027] Referring to the data in the above table, according to the comparison between Examples 1-3 and Comparative Examples 1-4, it can be known that the new material modified sound-absorbing panel of the present application has a good sound absorption effect and excellent flame retardant performance.
[0028] In the description of this specification, the descriptions referring to terms such as "one embodiment", "example", "specific example", etc. mean that the specific features, structures, materials, or characteristics described in connection with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described can be combined in a suitable manner in any one or more embodiments or examples.
[0029] The above content is only an example and illustration of the present invention. Those skilled in the art of the present technology can make various modifications or supplements to the described specific embodiments or use similar methods to replace them. As long as they do not deviate from the invention or exceed the scope defined by the present application, they should fall within the protection scope of the present invention.
Claims
1. A sound-absorbing panel for a new material-modified sound-insulating chamber, characterized in that, It comprises the following components in parts by weight: 20 - 36 parts of flame - retardant modified cellulose aerogel, 1.3 - 2.9 parts of calcium stearate, 40 - 48 parts of deionized water, 21 - 27 parts of epoxy resin, 2.5 - 4.5 parts of curing agent, 1.1 - 1.5 parts of sodium dodecyl sulfate, 0.8 - 1.2 parts of gelatin, and 0.3 - 0.5 parts of antioxidant; Among them, the flame - retardant modified cellulose aerogel is prepared by the following steps: Step a1: Dimethyl phosphite, dioxane, and acrylamide are stirred and reacted, and then a sodium methoxide - methanol solution is added dropwise with stirring. After the addition is complete, the reaction continues with stirring. After the reaction ends, the reaction product is cooled, then vacuum - filtered, and the filter cake is washed and dried to obtain an amino - containing phosphorus intermediate; Step a2: The amino - containing phosphorus intermediate, benzyltriethylammonium chloride, and epichlorohydrin are stirred and reacted, then the pH is adjusted with a sodium hydroxide solution, and then the reaction continues with stirring. After the reaction ends, the reaction product is cooled, then extracted, the extraction liquids are combined and dried, then vacuum - filtered, and the filtrate is rotary - evaporated to obtain a phosphorus - nitrogen cross - linker; Step a3: Sodium hydroxide, urea, and deionized water are stirred and reacted, then cotton wool and the phosphorus - nitrogen cross - linker are added and the reaction continues with stirring. After the reaction ends, the reaction product is cooled, then ultrasonically treated, and then poured into a mold and left to stand and solidify to obtain a phosphorus - nitrogen modified cellulose hydrogel; Step a4: The phosphorus - nitrogen modified cellulose hydrogel is successively soaked in a magnesium chloride solution and a sodium hydroxide solution, and then freeze - dried to obtain the flame - retardant modified cellulose aerogel.
2. The sound-absorbing panel of a new material modified sound insulation chamber according to claim 1, characterized in that, In step a1, the dosage ratio of dimethyl phosphite, dioxane, acrylamide, and the sodium methoxide - methanol solution is 10 mmol: 30 - 35 mL: 10 mmol: 3 - 5 mL.
3. The sound-absorbing panel of a new material modified sound insulation chamber according to claim 1, characterized in that, The sodium methoxide - methanol solution in step a1 is a solution formed by dissolving sodium methoxide at 0.5 - 1 g: 10 mL in anhydrous methanol.
4. A sound-absorbing panel for a new material modified sound insulation chamber according to claim 1, characterized in that, In step a2, the dosage ratio of the amino - containing phosphorus intermediate, benzyltriethylammonium chloride, and epichlorohydrin is 10 mmol: 0.05 - 0.15 g: 80 - 100 mmol.
5. The sound-absorbing panel of a new material modified soundproof chamber according to claim 1, characterized in that The mass fraction of the sodium hydroxide solution in step a2 is 30 - 40%.
6. The sound-absorbing panel of a new material modified sound insulation chamber according to claim 1, wherein In step a3, the dosage ratio of sodium hydroxide, urea, deionized water, cotton wool, and the phosphorus - nitrogen cross - linker is 3 - 4 g: 6 - 7 g: 40 - 45 mL: 5 g: 2.1 - 6.9 g.
7. The sound-absorbing panel of a new material-modified sound insulation chamber according to claim 1, characterized in that, In step a4, the dosage ratio of the phosphorus - nitrogen modified cellulose hydrogel, the magnesium chloride solution, and the sodium hydroxide solution is 5 g: 20 - 25 mL: 50 - 55 mL.
8. The sound-absorbing panel of the new material modified sound insulation chamber according to claim 1, characterized in that, In step a4, the molar concentration of the magnesium chloride solution is 0.5 - 1 mol / L; the mass fraction of the sodium hydroxide solution is 20 - 25%.
9. A method for preparing a sound-absorbing panel of a new material-modified sound-insulating chamber according to any one of claims 1-8, characterized in that, It includes the following steps: Step one: Weigh 20 - 36 parts of flame - retardant modified cellulose aerogel, 1.3 - 2.9 parts of calcium stearate, 40 - 48 parts of deionized water, 21 - 27 parts of epoxy resin, 2.5 - 4.5 parts of curing agent, 1.1 - 1.5 parts of sodium dodecyl sulfate, 0.8 - 1.2 parts of gelatin, and 0.3 - 0.5 parts of antioxidant in parts by weight for standby; Step 2: Add the flame-retardant modified cellulose aerogel, calcium stearate, and deionized water into a reaction kettle, stir and mix them for 30 - 60 min under the condition that the stirring rate is 600 - 800 r / min, then add epoxy resin, sodium dodecyl sulfate, gelatin, and antioxidant and continue to stir and mix for 30 - 40 min to form a mixed slurry; Step 3: Add the curing agent into the mixed slurry and continue to stir and mix for 10 - 15 min, then pour it into a mold, then place it in a vacuum drying oven, and then dry it for 2 - 4 h under the condition that the temperature is 60 - 70 °C. Take it out after curing and shaping, and trim it to remove the excess scraps and burrs to obtain the new material modified sound-absorbing panel for the sound insulation chamber.
10. The preparation method of a sound-absorbing panel for a new material modified sound insulation chamber according to claim 9, characterized in that, The epoxy resin is E-44 epoxy resin; the curing agent is 593 curing agent; the antioxidant is antioxidant 1010.
Citation Information
Patent Citations
Non-formaldehyde flame retardant for viscose fiber
CN101498103A
Hollow floating bead doped sound-absorption epoxy resin material and preparation method thereof
CN105419242A
Heat-preservation, heat-insulation and sound-absorption silicon dioxide aerogel composite material and preparation method thereof
CN116080194A
Microcrystalline PTT resin and preparation method thereof
CN120137361A
Non-MOCA type fitness equipment rubber coating material and preparation method thereof
CN120904509A